2010
DOI: 10.1080/09670260903171650
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and digalactosyldiacylglycerol composition of dinoflagellates. IV. Temperature-induced modulation of fatty acid regiochemistry as observed by electrospray ionization/mass spectrometry

Abstract: Members of the dinoflagellate genus Pyrocystis possess forms of mono-and digalactosyldiacylglycerol (MGDG and DGDG, respectively) that have the C 20 fatty acid eicosapentaenoic acid [20:5(n-3)] at the sn-1 position and either octadecapentaenoic acid [18:5(n-3)] or octadecatetraenoic acid [18:4(n-3)] at the sn-2 position. We have examined the effect of growth at 15 C, 20 C, and 25 C on modulation of the fatty acids associated with MGDG and DGDG in two strains of each of three species of Pyrocystis, P. fusifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Adlerstein et al It should be noted that polyunsaturated C 20 fatty acids are not typically abundant in the red algae, the Cyanidialeswhich contains P. cruentum -being among the exceptions Sato & Moriyama, 2007). Leblond et al (2010a) observed, in three different species of the C 20 /C 18 peridinin-containing dinoflagellate Pyrocystis, that fatty acid modulation according to growth temperature occurred consistently within the sn-2 fatty acid of DGDG. Within the C 20 / C 20 forms of MGDG and DGDG produced by C. velia, the same modulation of sn-2 fatty acid unsaturation level occurred, with a C 20:4 fatty acid being produced at 30°C but not at 20°C (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adlerstein et al It should be noted that polyunsaturated C 20 fatty acids are not typically abundant in the red algae, the Cyanidialeswhich contains P. cruentum -being among the exceptions Sato & Moriyama, 2007). Leblond et al (2010a) observed, in three different species of the C 20 /C 18 peridinin-containing dinoflagellate Pyrocystis, that fatty acid modulation according to growth temperature occurred consistently within the sn-2 fatty acid of DGDG. Within the C 20 / C 20 forms of MGDG and DGDG produced by C. velia, the same modulation of sn-2 fatty acid unsaturation level occurred, with a C 20:4 fatty acid being produced at 30°C but not at 20°C (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these two types of peridinin-containing dinoflagellates, a recent study on the forms of MGDG and DGDG present in Karenia brevis, Kryptoperidinium foliaceum and Lepidodinium chlorophorum -three non-peridinin-containing dinoflagellates of aberrant plastid ancestry -showed that these algae reflect to different degrees the fatty acid composition of their plastid ancestors, and in some cases show distinct differences from peridinin-containing species . A previous study (Leblond et al, 2010a) has also elucidated how species of Pyrocystis, which are Cluster 2 dinoflagellates, modulate their galactolipid-associated fatty acids in response to temperature. Thus, through the use of ESI/MS (and ESI/MS/MS) analyses, we now have a more complete picture of MGDG and DGDG composition in dinoflagellates than at any other time in the long history of lipid research.…”
Section: Introductionmentioning
confidence: 99%
“…Leblond and co-workers extensively studied the glycolipid profi les of dinofl agellate Pyrocystis spp., glaucocystophytes Cyanophora paradoxa and Glaucocystis nostochinearum , raphidophytes Chattonella , Fibrocapsa and Heterosigma spp. and chlororachinophytes Bigelowiella natans , Gymnochlora stellata and Lotharella spp., with the latter chlororachinophytic algae exhibiting a novel lauric acid containing MGDG (C20:5/C12:0, sn -1/ sn -2) (Leblond and Roche, 2009;Leblond et al , 2010a;Leblond et al , 2010b;Roche and Leblond, 2011). Wu et al .…”
Section: Recent Advances In Algal Lipid Methodology and Lipidomicsmentioning
confidence: 99%
“…Such an approach has illustrated that peridinin-containing dinoflagellates form discrete clusters according to the forms of MGDG and DGDG present (Gray et al, 2009), that the galactolipid composition of dinoflagellates containing aberrant plastids is similar to their plastidial ancestors (e.g. diatoms in the case of Kryptodinium foliaceum, green algae in Lepidodinium chlorophorum) with regard to the forms of MGDG and DGDG they possess , and how certain peridinin-containing dinoflagellates modulate the fatty acids of MGDG and DGDG according to growth temperature (Leblond et al, 2010). With rapidly advancing improvements in DNA sequencing technology, future studies on dinoflagellate genomes and transcriptomes will allow for the elucidation of the genetic underpinnings of MGDG and DGDG biosynthesis in photosynthetic dinoflagellates.…”
Section: Discussionmentioning
confidence: 99%